Innovation Development to Increase Local Competitive Advantage in Mojokerto Regency - Sri Juni Woro Astuti; Dwi Wahyu Prasetyono (Indonesian Association for Public Administration, 2017)
Becoming more competitive on the local and national levels can be seen as a strategy that will boost economic growth and, in turn, will improve the welfare of the community. Therefore, local government should make it a priority to draw up a grand plan for local development. The roles of resource-based and local potency in planning, therefore, become critical to improve the performance of local development. With accurate planning, the direction of regional development will be more focused. This paper will examine innovation strategy as an effort to increase local competitiveness, especially in Mojokerto Regency. This study utilizes a qualitative research method, where data is extracted from bureaucrats, community leaders, politicians, and academicians. Interactive data analysis methods, which take place continuously through the processes of data collection, data presentation, and conclusion are used to ensure well-considered results. Research indicates that the success of Mojokerto Regency in building local innovation can be attributed to the development of infrastructure and innovation in public services. This two-pronged approach to spearhead local development allowed Mojokerto Regency to increase its economic growth at an impressive rate. The strategies used to encourage the development of innovation at the local level are threefold, beginning with the alignment of regional development strategy to design long, medium, and short term innovation plans. Secondly, innovation is developed based on regional priorities that support economic growth in sectors that will benefit the wider community. Finally, the success of innovation in Mojokerto Regency is dependent on the support and commitment of local political leaders and apparatus resources.